Editorial - Panwar, Kuldeep; Joshi, Kamlesh; Singh, Satyendra; Bisht, Neeraj (Journal of Graphic Era University, 2023)
It is with great pleasure that we introduce this special issue on Latest Devel- opments in Computational Fluid Dynamics for the Journal of Graphic Era University published by River Publication. This Special Issue containing eight papers selected from the 34 received papers/abstracts. In modern engineering, Computational Fluid Dynamics (CFD) aspects are associated with many research areas Aviation, Turbo Machinery, Architecture, Process & Chemical Engineering, Heating & Refrigeration Engineering, Automobile & Train Design, Health Care, Petroleum Engineering and many more. Computational fluid dynamic sim- ulations (gas dynamics, fluid mechanics, bio-fluids, etc.), finite element simulations, and particle interaction simulations are applied regularly to study fluid-thermal, fluid-structure, and mechanical systems at various engineering scales. In addition, new computational methods and techniques are being developed to advance the state-of-the art in simulation capacity of various CFD tools. To capture the breath of applications and significant developments in modeling capability key papers have been selected for publication in the special issues. Papers chosen for this issue of GEJ are those that represent novel and leading work in the area of applying CFD to multiphase flow problems. All papers in this special issue were subject to the standard peer-reviewing process. We wish to thank the authors who have submitted their papers as per the journal guidelines and the reviewers who have contributed their time and efforts to improving the quality of the publication.